E-Customer Behavior Mediates Promotion on E-Commerce Purchase Decision MSME Industry - Fairuz Rifqi Abdurahman; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Harisandi, Prasetyo (PT. Riset Press International, 2024)
This research aims to explore the impact of promotions on e-commerce purchasing decisions among MSMEs in Indonesia. In addition, e-customer behavior is studied as a mediator of promotional activities and purchasing decisions. Data was collected from a total of 160 E-commerce users in Indonesia through structured questionnaires and hypothesis testing using the PLS model. These results validate that promotional activities have a significant influence on e-customer behavior and direct purchasing decisions. Purchasing decisions are directly influenced by e-customer behavior. In addition, e-customer behavior completely mediates the relationship between promotional activities and buyer decisions which has an indirect influence. In this study, the sample size was limited to 160 respondents, most of whom came from Jabodetabek, Indonesia. It is recommended that future research use larger sample sizes and include individuals from various industry sectors. Second, this research only focuses on promotions, purchasing decisions through e-customer behavior in MSME e-commerce. This research suggestion will help the e-commerce retail sector to build consumer trust, thereby increasing the e-commerce user base and increasing customer loyalty through various improvements so that it can meet your needs to understand